Preparation method of magnetic hydrogel robot based on two-photon doping printing
Prepare high -magnetic hydrogel robots with high magnetic and low biological toxicity through bi -photon doping technology, solve the problem of difficulty in achieving precise control in the biological environment in the biological environment, achieve more efficient and accurate exercise control, and reduce Biological toxicity of magnetic materials.
Patent Information
- Application Number
- CN202411482914.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-21
AI Technical Summary
It is difficult for software robots to achieve precise control in biological environments, and the commonly used neodymium iron boron magnetic materials will corrode and release harmful heavy metal ions in physiological environments.
Two-photon doping printing technology is used to prepare magnetic hydrogel robots with high residual magnetism and low biological toxicity. FePt nanoparticles are prepared through thermal reduction decomposition method, and hydrophilic groups are modified on their surface, combined with acrylic photosensitive hydrogel resin. Print to form micro soft robots with intelligent responsiveness.
It achieves more efficient and precise motion control in biological environments, reduces the biological toxicity of magnetic materials, and expands the application potential of microrobots in the biomedical field.
Smart Images

Figure CN119331161A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic soft robots, and in particular to a method for preparing a magnetic hydrogel robot based on two-photon doping printing. Background Art
[0002] Soft robots are robots that can perform tasks semi-autonomously or fully autonomously, especially at the millimeter level or below. Their adaptability and flexibility make them outstanding in small and complex environments, such as performing medical operations inside the human body. Such robots can enter areas that are difficult for traditional tools to reach, perform detection, diagnosis and treatment, and have broad application prospects in the medical field.
[0003] Due to the limitation of rigid components, traditional robots face the problem of poor environmental adaptability when applied in vivo. In contrast, soft robots can effectively reduce damage to tissues when in contact with biological tissues due to their modulus close to that of biological materials (about 104 to 109 Pa), and adapt to complex biological environments through continuous deformation, thus showing important potential in the biomedical field. Magnetic control actuation is a key actuation method for soft robots, and its behavior originates from the response of magnetic units in soft materials to external magnetic fields. When magnetic units (such as ferromagnetic or paramagnetic materials) are in a magnetic field, the magnetic units are affected by magnetic forces and magnetic torques. The magnetism of paramagnetic materials only exists under the action of an external magnetic field, and loses its magnetism once the magnetic field is removed; while ferromagnetic materials can maintain remanence in a magnetic field, and can still maintain a certain degree of magnetism even after the magnetic field is removed. The interaction between the remanence of ferromagnetic materials and the external magnetic field enables soft robots to achieve a variety of motion modes and deformation behaviors.
[0004] Nevertheless, soft robots still face some challenges in practical applications. First, in biological environments such as blood vessels, the impact of blood flow on robots makes precise control extremely challenging. Second, the commonly used NdFeB magnetic material will gradually corrode and release heavy metal neodymium ions with potential biotoxicity under physiological conditions, limiting its application in the biomedical field. Summary of the invention
[0005] In response to the above technical problems, the present invention discloses a method for preparing a magnetic hydrogel robot based on two-photon doping printing, which has high remanence and low biological toxicity, and increases the content of magnetic units in the soft robot, thereby achieving more efficient and precise movement. This will bring about a major breakthrough in the application of magnetically controlled microrobots in the biomedical field and promote their practical application in clinical medicine.
[0006] To this end, the technical solution adopted by the present invention is:
[0007] A method for preparing a magnetic hydrogel robot based on two-photon doping printing comprises the following steps:
[0008] Step S1, selecting an Fe source and a Pt source to mix, and adding a surfactant and a reaction inducer, wherein the molar ratio of the reaction inducer to the Pt source is 0.35-0.8:1, and preparing FePt nanoparticles with ferromagnetism by a thermal reduction decomposition method; modifying the surface of the FePt nanoparticles with hydrophilic groups by a ligand exchange reaction to obtain modified FePt nanoparticles;
[0009] Step S2, preparing acrylic photosensitive hydrogel resin;
[0010] Step S3, mixing acrylic photosensitive hydrogel resin with modified FePt nanoparticles to obtain magnetic hydrogel resin; using the magnetic hydrogel resin as the material, a two-photon printer is used to print a micro soft robot, and the obtained micro soft robot is magnetized to obtain a magnetic hydrogel robot.
[0011] In this technical solution, the ferromagnetic FePt nanoparticles prepared by thermal reduction decomposition method have excellent magnetic properties. The surface modification of FePt particles enhances the dispersion and uniformity of the material, making the robot more sensitive to response under the magnetic field, and can be precisely controlled to solve the problems of difficulty in driving and poor controllability of micro-robots in complex biological environments in the body. Acrylic photosensitive hydrogel resin is used, and then mixed with modified FePt nanoparticles. After printing and photocuring by a two-photon printer, it can deform in response to changes in the pH value of the external environment, shrink at low pH values, and expand at high pH values, giving the soft robot intelligent responsiveness, and the degree of deformation can be controlled by adjusting the laser parameters. The obtained robot is a composite material of hydrogel and modified FePt nanoparticles, with low biological toxicity, and can be used in the biomedical field.
[0012] Furthermore, the acrylic photosensitive hydrogel resin is obtained by adding a crosslinking agent, a photoinitiator and a thickener to acrylic monomers and mixing them.
[0013] As a further improvement of the present invention, the Fe source is iron pentacarbonyl, and the Pt source is platinum acetylacetonate.
[0014] As a further improvement of the present invention, step S1 includes:
[0015] Step S11, add platinum acetylacetonate, a surfactant and a reaction inducer into a reaction container, introduce an inert gas or nitrogen, mix well, then heat to 100-120° C., add pentacarbonyl iron; then heat to 300-350° C., keep warm for 3-5 hours to react; further, heat to 110° C., add pentacarbonyl iron;
[0016] Step S12, after the reaction is completed, washing the product FePt nanoparticles, and dispersing the washed FePt nanoparticles in a non-polar solvent to obtain a FePt particle dispersion;
[0017] Step S13, fully mixing the FePt particle dispersion with the β-mercaptoethylamine solution, stirring for 2-3 days, so that the hydrophilic groups are modified on the surface of the FePt particles, and washing to obtain modified FePt nanoparticles.
[0018] As a further improvement of the present invention, the molar ratio of platinum acetylacetonate to iron pentacarbonyl is 1:1.2-1.3. Furthermore, the molar ratio of platinum acetylacetonate to iron pentacarbonyl is 1:1.23-1.28. Using this technical solution, ferromagnetic FePt nanoparticles Fe 56 Pt 44 .
[0019] As a further improvement of the present invention, the surfactant is at least one of oleylamine or oleic acid. Further, the surfactant is oleylamine and oleic acid. Further preferably, the volume ratio of oleic acid to oleylamine is 1.0-3.0:50. Further preferably, the amount of oleic acid is 0.75-2.5 ml per mmol Pt. By adopting this technical solution, a suitable amount of oleic acid is selected to increase the crystal order and control particle agglomeration.
[0020] As a further improvement of the present invention, the ratio of the volume of the surfactant to the amount of platinum acetylacetonate is 40-60:0.001. Furthermore, the ratio of the volume of the surfactant to the amount of platinum acetylacetonate is 50-55:0.001.
[0021] As a further improvement of the present invention, the molar ratio of the reaction inducer to Pt is 0.35-0.8:1. As a further improvement of the present invention, the reaction inducer is hexadecyltrimethylammonium chloride. With this technical solution, hexadecyltrimethylammonium chloride can better promote Fe atoms and Pt atoms to form a face-centered tetragonal structure during the synthesis process, so that the prepared product has better ferromagnetism.
[0022] As a further improvement of the present invention, the heating rate of heating to 300-350° C. in step S11 is 2-10° C. / min; further, the heating rate is 5° C. / min.
[0023] As a further improvement of the present invention, in step S12, the product FePt nanoparticles are washed 2-3 times with a mixture of n-hexane and ethanol. Further preferably, the volume ratio of n-hexane to ethanol is 1:2.
[0024] As a further improvement of the present invention, the non-polar solvent is chloroform or the like.
[0025] As a further improvement of the present invention, the β-mercaptoethylamine solution is an alcohol solution of β-mercaptoethylamine. Further, the β-mercaptoethylamine solution is a methanol solution of β-mercaptoethylamine.
[0026] As a further improvement of the present invention, in step S13, the dosage ratio of β-mercaptoethylamine in the β-mercaptoethylamine solution to FePt particles in the FePt particle dispersion is 0.1-0.3mmol:40-60mg. Further, in step S13, the concentration of the β-mercaptoethylamine solution is 0.1-0.3M, the concentration of the FePt particle dispersion is 40-60mg / ml, and the volume ratio of the FePt particle dispersion to the β-mercaptoethylamine solution is 1:1.
[0027] As a further improvement of the present invention, in step S13, washing is performed in sequence using n-hexane+ethanol and water+ethanol.
[0028] As a further improvement of the present invention, the obtained modified FePt nanoparticles are added into ethyl lactate for dispersion.
[0029] As a further improvement of the present invention, in step S13, the stirring rate is 40-70 r / min.
[0030] As a further improvement of the present invention, step S2 comprises: adding copolymer monomers, thickeners, photoinitiators, crosslinking agents and sensitizers into acrylic acid, stirring and mixing the mixture uniformly.
[0031] As a further improvement of the present invention, the copolymer monomer is acrylamide, the thickener is polyvinyl pyrrolidone, the photoinitiator is tetraethyl Michler's ketone, the crosslinker is polydipentaerythritol pentaacrylate, and the sensitizer is triethanolamine. With this technical solution, the hydrogel has a more obvious difference in expansion and contraction rate at different pH values. Furthermore, the usage ratio of acrylamide to acrylic acid is 1-1.5 mg / ml.
[0032] As a further improvement of the present invention, in step S3, the mass ratio of the volume of acrylic photosensitive hydrogel resin to the modified FePt nanoparticles is 0.5 mL: 3-6 mg. Further, the modified FePt nanoparticles are first dispersed in ethyl lactate to obtain a modified FePt nanoparticle dispersion, which is then mixed with the acrylic photosensitive hydrogel resin.
[0033] Furthermore, the concentration of the modified FePt nanoparticle dispersion is 40-60 mg / ml, and the volume ratio of the acrylic photosensitive hydrogel resin to the FePt particle dispersion is 2-5:1.
[0034] Furthermore, acrylamide is dissolved in ethyl lactate to obtain an ethyl lactate solution of acrylamide, and then added. Furthermore, the ratio of acrylamide to ethyl lactate is 0.8-1.4 mg / ml.
[0035] As a further improvement of the present invention, in step S3, the acrylic photosensitive hydrogel resin and the modified FePt nanoparticles are mixed with a mixing degassing machine and subjected to ultrasonic dispersion treatment.
[0036] As a further improvement of the present invention, the magnetization in step S3 includes: placing the printed micro soft robot under a magnetizer and performing magnetization treatment at a magnetic field strength of 1.0-2.0T. Further, the magnetic field strength is 1.5T. Using this technical solution, the robot is given magnetism, the printed robot is placed in a groove, and deionized water is added; the groove is placed under a rotating magnetic field of a three-axis Helmholtz coil, and the robot can achieve tumbling motion under the action of the magnetic field. The robot realizes magnetic control drive under magnetic field conditions.
[0037] As a further improvement of the present invention, in step S3, the laser power of the two-photon printer is 28-60mW, and the scanning rate is 7500-12000μm / s. Further, the laser power of the two-photon printer is 35-55mW; further, the scanning rate is 9000-12000μm / s. Further preferably, the laser power of the two-photon printer is 40mW; further, the scanning rate is 10000μm / s. By adopting this technical solution, by selecting appropriate laser power and scanning speed, the degree of cross-linking of the hydrogel can be accurately controlled to cause non-uniform expansion and contraction, thereby achieving the desired structural deformation.
[0038] Furthermore, the scanning rate is 8000 μm / s, the upper layer power is 28-30 mW, and the lower layer power is 50-60 mW. By adopting this technical solution, the robot can produce a good deformation effect (bending upward).
[0039] The present invention also discloses a magnetic hydrogel robot, which is prepared by using any of the above methods for preparing a magnetic hydrogel robot based on two-photon doping printing.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] First, the ferromagnetic FePt nanoparticles prepared by the technical solution of the present invention through the thermal reduction decomposition method are small in size and have excellent magnetic properties, such as high saturation magnetization and moderate remanence, which improves the robot's responsiveness under a magnetic field. Secondly, the surface modification of the FePt particles uses β-mercaptoethylamine to improve the hydrophilicity of the particles and enhance the dispersibility and uniformity of the material. The materials obtained based on the above improvements, combined with the two-photon printing technology, ensure the high-precision manufacturing of the microrobot, and can accurately control the structural details and functions. Moreover, it can be magnetized by a magnetizer so that it can be precisely operated under the control of an external magnetic field.
[0042] Second, the photocurable hydrogel resin prepared by the technical solution of the present invention can not only be photocured under laser scanning, but also has pH responsiveness and can achieve shape deformation under different environments, thereby expanding the scope of application. The technical solution of the present invention provides reference significance in terms of high-precision manufacturing, intelligent response and function optimization process flow, and provides an important reference for the research and development of microrobots and functional materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The present invention is a flow chart for preparing the magnetic hydrogel robot.
[0044] Figure 2 Schematic diagram of the two-photon printing magnetic composite material of the present invention.
[0045] Figure 3 Transmission electron microscope photograph and particle size distribution curve of ferromagnetic FePt nanoparticles (oleic acid addition amount is 2.5 mL) prepared in Example 1 of the present invention; wherein, (a) is a transmission electron microscope photograph, and (b) is a particle size distribution curve.
[0046] Figure 4 This is a hysteresis curve diagram of the ferromagnetic FePt nanoparticles (the amount of oleic acid added is 2.5 mL) prepared in Example 1 of the present invention.
[0047] Figure 5 This is a microscopic photograph of the spiral magnetic soft robot after printing in Example 1 of the present invention.
[0048] Figure 6 Transmission electron microscope photograph and particle size distribution curve of ferromagnetic FePt nanoparticles (oleic acid addition amount is 1.67 mL) prepared in Example 2 of the present invention; wherein, (a) is a transmission electron microscope photograph, and (b) is a particle size distribution curve.
[0049] Figure 7 This is a hysteresis curve diagram of the ferromagnetic FePt nanoparticles prepared in Example 2 of the present invention (the amount of oleic acid added is 1.67 mL).
[0050] Figure 8 This is the energy scattering spectrum of the ferromagnetic FePt nanoparticles prepared in Example 2 of the present invention (the amount of oleic acid added is 1.67 mL).
[0051] Fig. 9 The expansion and contraction of the hydrogel in Example 2 of the present invention at different pH values.
[0052] Fig.10 This is the motion trajectory of the soft robot in Example 2 of the present invention under the control of the magnetic field.
[0053] Fig.11 This is a comparison chart of the shrinkage rate of the hydrogel after curing obtained with different laser powers LP and scanning rates SS in Example 3 of the present invention. DETAILED DESCRIPTION
[0054] The preferred embodiments of the present invention are described in further detail below.
[0055] A method for preparing a magnetic hydrogel robot based on two-photon doping printing, such as Figure 1 and Figure 2 As shown, the following steps are included:
[0056] Step S1, preparation of ferromagnetic FePt particles: selecting pentacarbonyl iron and platinum acetylacetonate as Fe source and Pt source respectively, adding surfactant and reaction inducer, and preparing FePt nanoparticles with ferromagnetism by thermal reduction decomposition method, and then modifying hydrophilic groups on the surface of the particles by ligand exchange reaction to prepare hydrophilic ferromagnetic nanoparticles;
[0057] Step S2, preparing pH-responsive photocurable hydrogel resin: based on acrylic monomers, adding crosslinking agents, photoinitiators, thickeners, etc. to obtain photosensitive hydrogel resin, polymerizing and molding by two-photon printing technology, which can deform in response to changes in the pH value of the external environment, shrink at low pH values, and expand at high pH values;
[0058] Step S3, doping manufacturing and magnetic control drive of micro soft robots: blending hydrogel and modified FePt nanoparticles to obtain magnetic hydrogel resin, printing and preparing the micro soft robot structure, and magnetizing the soft robot. The soft robot can achieve different movement modes under different magnetic field conditions.
[0059] The step S1 of preparing ferromagnetic FePt particles comprises:
[0060] S11: adding platinum acetylacetonate, a surfactant and a reaction inducing agent into a reaction container and mixing them evenly;
[0061] S12: heating the reaction system to 110° C. and adding iron pentacarbonyl;
[0062] S13: heating the reaction system to a temperature in the range of 300-350° C. at a uniform heating rate and keeping the temperature for 3-5 hours;
[0063] S14: After the reaction is completed, the particles are washed 2-3 times with a mixed solution of ethanol and n-hexane, and the FePt nanoparticles are finally dispersed in a non-polar solvent;
[0064] S15: The FePt particle dispersion and the β-mercaptoethylamine solution are fully mixed and vigorously stirred for 2-3 days, so that the hydrophilic group (amine group) is successfully modified on the surface of the FePt particles.
[0065] In step S11, the surfactants are oleylamine and oleic acid, and the reaction inducing agent is hexadecyltrimethylammonium chloride.
[0066] The step S2 of preparing a pH-responsive light-curable hydrogel resin comprises:
[0067] S21: Add copolymer monomer, thickener, photoinitiator, crosslinker, and sensitizer to acrylic acid, and stir overnight to ensure that all ingredients are evenly mixed.
[0068] For the prepared hydrogel resin, in order to detect its pH response after 3D printing light curing, the resin was operated as follows:
[0069] The PPGT2 two-photon 3D printer produced by Nanoscribe of Germany was selected to print the prepared photocurable hydrogel resin; the printing process was carried out with a thickness of 0.16 mm and a size of 22×22 mm. 2 The printing was carried out on a glass slide, and a cylindrical array with a bottom diameter of 50 μm and a height of 70 μm was printed. The laser power was set to 40 mW and the scanning speed was 100 mm / s. After printing, the glass slide was immersed in a propylene glycol methyl ether acetate solution and then transferred to 99.5% isopropyl alcohol for immersion to remove the uncured hydrogel resin.
[0070] The printed cylindrical arrays were placed in solutions with different pH values, their deformation behaviors were observed, the pH response range of the hydrogel was found, and curves were drawn based on the expansion and contraction rates of the hydrogel at different pH values;
[0071] In step S21, the copolymer monomer is acrylamide, the thickener is polyvinyl pyrrolidone, the photoinitiator is tetraethyl Michler's ketone, the crosslinking agent is polydipentaerythritol pentaacrylate, and the sensitizer is triethanolamine.
[0072] Step S3: doping manufacturing and magnetic control driving of the micro soft robot includes:
[0073] S31: mixing the hydrogel with modified FePt nanoparticles to prepare a magnetic composite printing material;
[0074] S32: Using a two-photon printer, printing the magnetic composite printing material into a desired structure;
[0075] S33: placing the printed structure under a magnetizer and setting the magnetization magnetic field strength to about 1.5T for magnetization treatment.
[0076] The magnetized robot is subjected to magnetic field conditions to carry out magnetic control driving experiments, including:
[0077] S341: placing the magnetized fixture structure into the groove and adding deionized water;
[0078] S342: The groove is placed under the rotating magnetic field of the three-axis Helmholtz coil, and the printed structure realizes tumbling motion under the action of the magnetic field.
[0079] The following describes the invention in conjunction with specific embodiments.
[0080] Example 1
[0081] A method for preparing a magnetic hydrogel robot based on two-photon doping printing comprises the following steps:
[0082] (1) Add 0.393 g of platinum acetylacetonate, 0.16 g of hexadecyltrimethylammonium chloride, and 2.5 mL of oleic acid to 50 mL of oleylamine and continue to flow N 2 The system was heated to 110 °C and the N 2 , add 0.162mL of pentacarbonyl iron; then heat the system to 350℃ at a heating rate of 5℃ / min and keep it warm for 3h. After the reaction, take 10mL of the reaction solution and add it to 25mL of ethanol, centrifuge and wash the precipitate twice with a mixture of n-hexane and ethanol (volume ratio 1:2), and finally disperse the FePt particles in 5mL of chloroform to obtain a chloroform dispersion of FePt particles.
[0083] The transmission electron microscopy images and particle size statistical analysis of the FePt nanoparticles obtained in the above steps are as follows: Figure 3 Its hysteresis curve is shown as Figure 4 As shown, it can be seen that the FePt particles prepared in this embodiment have a particle size of about 6 nm, a saturation magnetization of 57 emu / g, a residual magnetization of 18 emu / g, and a coercive force of 0.53 kOe.
[0084] Weigh 0.1915g of β-mercaptoethylamine and dissolve it in 5mL of methanol, and stir evenly until it is completely dissolved. Subsequently, add 5mL of the prepared chloroform dispersion of FePt particles to the solution and stir at a stirring speed of 50rpm for 48 hours. Then, add 10mL of n-hexane and 15mL of ethanol to the reaction solution in sequence for two washes. Subsequently, add 10mL of deionized water and 20mL of ethanol for two washes. Finally, dissolve the FePt particles modified with β-mercaptoethylamine in ethyl lactate.
[0085] (2) Dissolve 10g acrylamide in 10mL ethyl lactate, then add 8mL acrylic acid and mix well. Then, slowly add 2g polyvinyl pyrrolidone (PVP, molecular weight 130,000) and stir until completely dissolved. Then, take 2.5mL of the above solution into a brown reagent bottle, use a syringe to add 0.4mL polydipentaerythritol pentaacrylate solution, 0.5mL triethanolamine solution and 0.1mL EMK / DMF (weight ratio 20%) mixed solution, stir well, and ensure that it is completely protected from light during this process, and finally obtain a light-cured hydrogel resin.
[0086] The PPGT2 two-photon 3D printer produced by Nanoscribe of Germany was selected to print the prepared photocurable hydrogel resin. The printing process was carried out with a thickness of 0.16 mm and a size of 22×22 mm. 2 The printing is carried out on a glass slide. When the laser power is higher and the scanning speed is slower, the degree of photocuring of the hydrogel is higher and the printing effect is better.
[0087] (3) 0.5 mL of photocurable hydrogel resin was placed in a centrifuge tube, and 100 μL of FePt particle dispersion (mass concentration was about 60 mg / mL) was added. Mixing was performed using a mixing and degassing machine model AR-100 for 4-5 minutes. Subsequently, the mixture was placed in an ultrasonic cleaning machine for ultrasonic treatment for 10-30 minutes to finally obtain a uniformly mixed magnetic composite printing material.
[0088] The PPGT2 two-photon 3D printer produced by Nanoscribe of Germany was selected to print the prepared magnetic composite printing material. The printing process was carried out with a thickness of 0.16 mm and a size of 22×22 mm. 2 The printing was performed on a glass slide with a laser power of 40 mW and a scanning speed of 10,000 μm / s. After printing, the glass slide was immersed in the PGMEA solution for 5 minutes and then transferred to 99.5% isopropanol for 15 minutes to remove the uncured hydrogel solution. Figure 5 shown.
[0089] Next, the processed soft robot is placed in a magnetizer, and the magnetizing voltage is set to 1250V for magnetization treatment, and finally a magnetized micro soft robot is obtained.
[0090] Example 2
[0091] Based on Example 1, Example 2 makes corresponding adjustments to the reaction raw materials and their contents. The specific experimental steps are as follows:
[0092] (1) Preparation of ferromagnetic FePt particles: Iron pentacarbonyl and platinum acetylacetonate were selected as the Fe source and Pt source, respectively, and the thermal reduction decomposition method was used to prepare ferromagnetic FePt nanoparticles. β-mercaptoethanol was further modified on the surface of the particles, and hydroxyl groups were modified on the surface of the FePt particles through ligand reaction, thereby improving the hydrophilicity of the particles.
[0093] The preparation process is as follows: 0.393 g of platinum acetylacetonate, 0.16 g of benzyltriethylammonium chloride, and 1.67 mL of oleic acid are added to 50 mL of oleylamine, and N 2 The system was heated to 110 °C and the N 2 , add 0.162mL of pentacarbonyl iron; then heat the system to 350℃ at a heating rate of 5℃ / min and keep warm for 3h. After the reaction, take 10mL of the reaction solution and add it to 25mL of ethanol, centrifuge and take the precipitate and wash it twice with a mixture of n-hexane and ethanol (volume ratio 1:2), and finally disperse the FePt particles in 5mL of chloroform. Transmission electron microscopy photos of FePt nanoparticles and particle size statistical analysis are shown in Figure 6 Its hysteresis curve is shown as Figure 7 As shown, the energy scattering spectrum analysis results are as follows Figure 8 shown.
[0094] Weigh and dissolve 0.115g of β-mercaptoethanol in 5mL of methanol and stir evenly until completely dissolved. Subsequently, add 5mL of the prepared FePt chloroform solution to the solution and stir at 70rpm for 48 hours. Next, add 10mL of n-hexane and 15mL of ethanol to the reaction solution in sequence for two washes. Subsequently, add 10mL of deionized water and 20mL of ethanol for two washes. Finally, dissolve the FePt particles modified with β-mercaptoethylamine in ethyl lactate.
[0095] (2) Preparation of pH-responsive photocurable hydrogel resin: A photosensitive hydrogel solution is prepared using acrylic acid and N,N-dimethylacrylamide as monomers. The hydrogel can undergo photocuring reaction under laser scanning conditions. In particular, the hydrogel is also pH-responsive, that is, its volume will expand or shrink with changes in the pH value of the environment, thereby achieving shape deformation.
[0096] The preparation process is as follows: dissolve 10g N,N-dimethylacrylamide in 8mL ethyl lactate, then add 8mL acrylic acid and mix well. Next, slowly add 1.5g polyvinyl pyrrolidone (PVP, molecular weight 130,000) and stir until completely dissolved. Then, take 2.5mL of the above solution in a brown reagent bottle, use a syringe to add 0.4mL polydipentaerythritol pentaacrylate solution, 0.5mL triethanolamine solution and 0.1mL EMK / DMF (weight ratio 20%) mixed solution, stir well, and ensure that it is completely protected from light during this process, and finally obtain a light-cured hydrogel resin.
[0097] The PPGT2 two-photon 3D printer produced by Nanoscribe of Germany was selected to print the prepared photocurable hydrogel resin. The printing process was carried out with a thickness of 0.16 mm and a size of 22×22 mm. 2 The laser power was set to 40 mW, the scanning speed was 100 mm / s, and a cylindrical array with a bottom diameter of 50 μm and a height of 70 μm was printed. After printing, the cylindrical array was placed in solutions with pH values of 1-13. The cross-sectional shrinkage diagram is shown in Figure 2. Fig. 9 The relationship between the swelling and shrinking behavior of hydrogels and the pH value of the environment is shown in Fig. 9 shown.
[0098] (3) Doping manufacturing and magnetic control drive of micro soft robots: Use a two-photon printer to print micro soft robots with the required structure. After printing, these soft robots are placed in a magnetizer for magnetization, thus giving the micro robots the characteristics of magnetic programmability.
[0099] The preparation process is as follows: 0.5 mL of hydrogel is placed in a centrifuge tube, and 100 μL of FePt particle dispersion (mass concentration is about 60 mg / mL) is added. Mixing is performed using a mixing and degassing machine model AR-100 for 4-5 minutes. Subsequently, the mixture is placed in an ultrasonic cleaner for ultrasonic treatment for 30 minutes, and finally a uniformly mixed magnetic composite printing material is obtained.
[0100] The PPGT2 two-photon 3D printer produced by Nanoscribe of Germany was selected to print the prepared magnetic composite printing material. The printing process was carried out with a thickness of 0.16 mm and a size of 22×22 mm. 2 The laser power was set to 40 mW and the scanning speed was 100 mm / s. After printing, the glass slide was immersed in the PGMEA solution for 5 minutes and then transferred to 99.5% isopropanol for 15 minutes to remove the uncured hydrogel solution.
[0101] Next, the processed soft robot is placed in a magnetizer, and the magnetizing voltage is set to 1250V for magnetization treatment, and finally a magnetized micro soft robot is obtained.
[0102] The magnetized soft robot was placed in a rotating magnetic field of a three-axis Helmholtz coil, with a magnetic field strength of 8 mT and a frequency of 1 Hz. Under a microscope, it was observed that the soft robot had a good magnetic response effect and could roll along a pre-designed rectangular trajectory, such as Fig.10 shown.
[0103] Example 3
[0104] On the basis of Example 1, in order to investigate the influence of printing parameters on the curing degree of the photocurable hydrogel resin, after obtaining the photocurable hydrogel resin in step (2), the printing parameters of the two-photon printer were changed, specifically the laser power LP and the scanning rate SS were changed, the power was 30-80 mW, and the scanning rate was 6000-12000 μm / s. The shrinkage of the hydrogel obtained after curing with different laser powers LP and scanning rates SS is shown in the figure. Fig.11 As shown; wherein, the ordinate is the shrinkage rate, and the calculation formula is shrinkage = (ab) / a, a: the cross-sectional area of the hydrogel cylinder after development under pure water; b: the cross-sectional area of the hydrogel placed in a strong acidic environment (after shrinkage).
[0105] The degree of cross-linking of hydrogels significantly affects their expansion and contraction behavior. Generally, the higher the degree of cross-linking, the stronger the hydrogel's resistance to deformation, and therefore the smaller the expansion and contraction amplitude; conversely, the lower the degree of cross-linking, the weaker the hydrogel's resistance, and the greater the expansion and contraction amplitude. During the photocuring process, laser power and scanning speed are the main factors affecting the degree of cross-linking of hydrogels.
[0106] like Fig.11 As shown, by adjusting the printing parameters (such as laser power LP and scanning rate SS), the cross-linking degree of the hydrogel can be precisely controlled to produce non-uniform expansion and contraction, thereby achieving the desired structural deformation.
[0107] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing a magnetic hydrogel robot based on two-photon doping printing, characterized in that: The steps include: Step S1, selecting an Fe source and a Pt source to mix, adding a surfactant and a reaction inducer, and adopting a thermal reduction decomposition method to prepare FePt nanoparticles with ferromagnetism; modifying the surface of the FePt nanoparticles with hydrophilic groups through a ligand exchange reaction to obtain modified FePt nanoparticles; Step S2, preparing acrylic photosensitive hydrogel resin; Step S3, mixing acrylic photosensitive hydrogel resin with modified FePt nanoparticles to obtain magnetic hydrogel resin; using the magnetic hydrogel resin as the material, a two-photon printer is used to print a micro soft robot, and the obtained micro soft robot is magnetized to obtain a magnetic hydrogel robot.
2. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 1, characterized in that: The Fe source is iron pentacarbonyl, and the Pt source is platinum acetylacetonate.
3. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 2, characterized in that: Step S1 includes: Step S11, adding platinum acetylacetonate, a surfactant and a reaction inducer into a reaction container, introducing an inert gas or nitrogen, mixing evenly, then heating to 100-120° C., adding pentacarbonyl iron; then heating to 300-350° C., keeping the temperature for 3-5 hours to react; wherein the molar ratio of platinum acetylacetonate to pentacarbonyl iron is 1:1.2-1.3; Step S12, after the reaction is completed, washing the product FePt nanoparticles, and dispersing the washed FePt nanoparticles in a non-polar solvent to obtain a FePt particle dispersion; Step S13, fully mixing the FePt particle dispersion with the β-mercaptoethylamine solution, stirring for 2-3 days, so that the hydrophilic groups are modified on the surface of the FePt particles, and washing to obtain modified FePt nanoparticles.
4. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 3, characterized in that: The surfactant includes oleic acid and oleylamine, and the amount of the oleic acid per mmolPt is 0.75-2.5 ml; the reaction inducer is hexadecyltrimethylammonium chloride; the molar ratio of the reaction inducer to Pt is 0.35-0.8:1; in step S13, the amount ratio of β-mercaptoethylamine in the β-mercaptoethylamine solution to the FePt particles in the FePt particle dispersion is 0.1-0.3 mmol:40-60 mg.
5. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 1, characterized in that: Step S2 comprises: adding copolymer monomer, thickener, photoinitiator, crosslinker and sensitizer to acrylic acid, stirring and mixing evenly; the copolymer monomer is acrylamide, the thickener is polyvinyl pyrrolidone, the photoinitiator is tetraethyl Michler's ketone, the crosslinker is polydipentaerythritol pentaacrylate, and the sensitizer is triethanolamine; the usage ratio of acrylamide to acrylic acid is 1-1.5 mg / ml.
6. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 1, characterized in that: In step S3, the mass ratio of the volume of acrylic photosensitive hydrogel resin to the modified FePt nanoparticles is 0.5 mL: 3-6 mg.
7. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 1, characterized in that: The magnetization in step S3 includes: placing the printed micro soft robot under a magnetizer and performing magnetization treatment at a magnetic field strength of 1.0-2.0T.
8. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 7, characterized in that: The magnetic field strength is 1.5T.
9. The method for preparing a magnetic hydrogel robot based on two-photon doping printing according to claim 7, characterized in that: In step S3, the laser power of the two-photon printer is 28-60 mW, and the scanning rate is 7500-12000 μm / s.
10. A magnetic hydrogel robot, characterized in that: The magnetic hydrogel robot is prepared by the preparation method of the magnetic hydrogel robot based on two-photon doping printing as described in any one of claims 1 to 9.
Citation Information
Cited By
Micro-robot cluster capable of simultaneously delivering multiple drugs in targeted manner and preparation method of micro-robot cluster
CN120093710A